THE ROLE OF CORPORATE SOCIAL RESPONSIBILITY (CSR) INITIATIVES IN PROMOTING WOMEN EMPOWERMENT IN INDIA - Rajawat, Akshita; Shukla, Kedar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study explores the transformative impact of Corporate Social Responsibility (CSR) initiatives on women’s socio-economic status and empowerment across diverse regions and sectors. Through primary data collection, the study provides an in-depth analysis of how various CSR strategies affect women’s economic conditions and their overall empowerment. The results reveal significant variations in the effectiveness of these initiatives, influenced by regional and sectoral contexts. Key successful strategies are identified, demonstrating the potential of CSR programs to drive meaningful socio-economic improvements for women. This study highlights the critical importance of designing CSR interventions that are tailored to the unique needs and conditions of different regions and sectors, ensuring maximum positive impact on women’s socio- economic development and empowerment. Companies are developing and implementing CSR initiatives that empower women because they understand the significant impact gender parity has on organizational success and societal growth. The goal is to determine which approaches are most beneficial in promoting the professional and personal growth of women. Additionally, the study will evaluate the concrete results of these endeavors while also investigating the obstacles and constraints encountered by organizations. It will analyze CSR in depth to provide beneficial insights into how it may be used to empower women and contribute to gender equality initiatives. The goal is to make these gains meaningful and sustainable. Corporate social responsibility (CSR) initiatives that aim to empower women show a sea change in how corporations feel about gender equality. It shows that people realize that empowering women is crucial for society as a whole and for businesses to be more sustainable. Businesses are constantly improving their methods, and these initiatives will have a significant influence on how gender equality and economic development are shaped in the future. Corporate social responsibility (CSR) initiatives that prioritize women’s empowerment should use a multi-pronged approach, tackling both structural obstacles and employees’ specific areas of growth. Supportive environments that promote gender equality and increase opportunities for women can be created by businesses through the integration of targeted activities into their CSR programs. These tactics not only aid women in climbing the corporate ladder, but they also have a positive impact on society as a whole. Companies may make a significant difference in women’s empowerment through their CSR initiatives. Women empowerment is not merely a slogan but a prerequisite for an optimal capacity for overall development of a family, society, nation and a sustainable world. The study emphasizes the need of organizations committing to women’s empowerment and constantly evaluating and improving their methods to tackle new issues and make the most of their effect. Companies can improve their CSR initiatives and have a significant impact on organizational performance and society advancement by implementing the best practices found in this research.